2021
DOI: 10.1002/jev2.12046
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Mycobacterium tuberculosis is associated to a SIGLEC1 null variant that limits antigen exchange via trafficking extracellular vesicles

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Additionally, an increase in bacterial burden was observed and the authors proposed a local type I IFN signaling pathway driving CD169 expression, but the source of type I IFN could not be elucidated (51). Lastly, results from knockout experiments on CD169 in Mycobacterium tuberculosis infection suggest that the receptor is responsible for the retainment of extracellular vesicles deriving from infected cells resulting in early antiviral immune activation (52).…”
Section: Molecular Characteristics and Potential Contributions In Imm...mentioning
confidence: 99%
“…Additionally, an increase in bacterial burden was observed and the authors proposed a local type I IFN signaling pathway driving CD169 expression, but the source of type I IFN could not be elucidated (51). Lastly, results from knockout experiments on CD169 in Mycobacterium tuberculosis infection suggest that the receptor is responsible for the retainment of extracellular vesicles deriving from infected cells resulting in early antiviral immune activation (52).…”
Section: Molecular Characteristics and Potential Contributions In Imm...mentioning
confidence: 99%
“…Thus, Siglec-1 nanoclustering may have a different impact in the capture of particulate antigens depending on their structural properties. This possibility can extend the relevance of Siglec-1 spatial organization to other immunological processes like antigen presentation of MHC-I and MHC-II/antigen complexes captured from secreted exosomes (André et al, 2004; Benet et al, 2021; Chaput et al, 2004; Segura et al, 2007; Théry et al, 2002; Wakim and Bevan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mtb infection induced the local spread of bacteria within the lung of CD169 deficient mice, resulting in more extensive pathogenic lesions than wild-type mice. In the same study, human DCs activated T cells by the uptake of extracellular vesicles purified from Mtb-infected THP-1-derived macrophages in a CD169 dependent manner ( Benet et al., 2021 ). It has been recently reported that CD169 on macrophages preferentially binds to and interacts with CD8α + cDCs for CD8 + T cell cross-priming ( Van Dinther et al., 2018 ), suggesting the importance of the interaction between DCs and macrophages in CD8 + T cell immunity formation in TB pathogenesis.…”
Section: Interaction With Various Cellsmentioning
confidence: 97%
“…reported that nuoG of Mtb, which encodes a subunit of the type I nicotinamide adenine dinucleotide (NADH) dehydrogenase complex, inhibits Mtb-infected macrophage apoptosis, and the infection of macrophages with the nuoG- deleted Mtb mutant induced increased macrophage apoptosis in vitro and increased macrophage survival with controlled bacterial burden and lung pathology in in vivo mouse studies ( Velmurugan et al., 2007 ) ( Figure 1D ). Recently, it was confirmed that a single-nucleotide polymorphism of Siglec-1 (CD169), a cell adhesion and endocytic receptor that recognizes sialylated glycans, was correlated with extrapulmonary dissemination of Mtb ( Benet et al., 2021 ), susceptibility to Mtb infection, and activation of pulmonary TB in human cohort studies ( Souza De Lima et al., 2017 ). Mtb infection induced the local spread of bacteria within the lung of CD169 deficient mice, resulting in more extensive pathogenic lesions than wild-type mice.…”
Section: Interaction With Various Cellsmentioning
confidence: 98%